Towards an integrated online learning system for microscopic pathology: Two teaching examples - Kainulainen Mikko; Helle Laura; Kronqvist Pauliina; Vincken Koen L.; Pawelka Friedrich; Korpinen Katarina; de Leng Bas (Germany, 2025)
Microscopy is an essential basis for exploring and understanding pathological disease
mechanisms. As a discipline, pathology is highly dependent on visual imaging technologies.
Currently, digital pathology is a standard method with special advantages in both clinical
histopathological diagnostics as well as the education of (undergraduate and postgraduate)
medical students and pathology residents. However, to date, the available digital applications
lack features to optimally support online collaborative learning and teaching of
histopathology, such as possibilities for learners to individually perform tasks (e.g. annotate)
on digital slides, opportunities for groups to reflect on their work and to receive feedback
from more knowledgeable peers or supervisors. Such shortcomings have recently become
more imminent, due to shifts toward more online learning in pathology education. Therefore,
the cLovid (collaborative learning of viewing and decision-making skills) project set out to
build an integrated online learning system featuring
-an open-source webmicroscope (an extension to the OMERO viewer) with enhanced features for annotating whole-slide images, allowing integration with assessment and feedback software;
-an online assessment software—e.g., VQuest, in our design—for constructing assignments using various types of responses (e.g. marker questions, which are ideal for visual domains), suitable for developing image interpretation skills through active learning with large images;
-an open-source software dashboard (PRISMA) for synthesizing and visualizing students’ responses in tasks using various types of responses, allowing teachers to provide collective feedback to groups of students, as well as a joint platform for communication for both on-site and remote settings.
Subsequently, the project team carried out two teaching pilots to demonstrate how this
system can be used for teaching with guided activity, collaboration, feedback, reflection and
possibilities for the teachers to model diagnostic reasoning. The teaching examples involved
the pathology curriculum of second-year undergraduate medical students (N=70) in two
European universities and the training of pathology residents (N=16) in Finland. In this
paper, we present the development of the integrated system for online teaching and learning
of histopathology and exemplify its use in the two scenarios. Lessons learned from the
teaching pilots will be discussed.
Proceedings of the Technology-Enhanced Learning in Laboratories Workshop (TELL 2023). CEUR Workshop Proceedings, Vol. 3393